Comparison of methods for deriving desorption activation energy. (May 2015) - Knizikevičius, R.
Abstract: The chemical etching of intrinsic silicon in Br2 ambient is considered. The theoretically calculated dependences of silicon etching rates on pressure of Br2 molecules at different temperatures are compared with experimentally measured. Desorption rate constants, found by fitting the experimental data, are used for comparison of Arrhenius plots based on three different interpretations of pre-exponential factor. It is determined that desorption activation energy of SiBr2 molecules differs up to 30% when different prefactors are used. Highlights: Three Arrhenius plots for deriving desorption activation energy are compared. Desorption activation energy depends on the interpretation of pre-exponential factor. Transition state theory significantly improves accuracy of the obtained results.